Land-cover changes predict steep declines for the Sumatran orangutan (Pongo abelii) - Wich, S.A.; Singleton, I.; Nowak, M.G.; Atmoko, S.S.U.; Nisam, G.; Arif, S.M.; Putra, R.H.; Ardi, R.; Fredriksson, G.; Usher, G.; Gaveau, D.L.A.; Kühl, H.S. (American Association for the Advancement of Science, 2016)
New surveys provide higher estimate of Sumatran orangutans than previously, but future scenarios indicate decline continues.